Variations in weight stigma concerns - Jessica E. Cornick; Cambridge Teter; Andrew K. Thaw (Health Psychology Research, 2016)
Over the past 40 years, obesity rates in the United States have grown significantly; these rates have not grown uniformly across the United States (18 of the 20 counties with the highest obesity rates are located in the South). Obesity increases cardiovascular disease risk factors and new research has highlighted the negative psychological effects of obesity, known as weight stigma, including decreased selfcontrol resources, over eating, and exercise avoidance. The primary objective of this study was to determine if weight stigma concerns varied regionally and if social behaviors influenced this variation. In two studies, we collected cross-sectional data from participants in the United States including height and weight, weight stigma concerns, and perception of friends’ preoccupation with weight and dieting. We also collected each participant’s home zip code which was used to locate local obesity rate. We established differences in the relationship between body mass index and weight stigma concerns by local county obesity rate and showed that perceived friend preoccupation with weight and dieting mediated this relationship for individuals in low and medium obesity rate counties. For individuals living in United States counties with lower levels of obesity, increases in personal body mass index leads to increased weight stigma concerns due to an increase in perceived friend preoccupation with weight and dieting. These results indicate that relationships between body mass index, weight stigma concerns, and social networks vary significantly for subpopulations throughout the United States.